2015
DOI: 10.1016/j.ijid.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Severe bacterial infections in patients with non-transfusion-dependent thalassemia: prevalence and clinical risk factors

Abstract: The prevalence of bacterial infection in patients with NTDT was found to be moderate. Time after splenectomy >10 years, deferoxamine therapy, and iron overload may be clinical risk factors for severe bacterial infection in patients with NTDT. Bacterial infection should be recognized in splenectomized patients with NTDT, particularly those who have an iron overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…Overall rate of infections per year in the present study was 3.03 ± 0.45 per year per patient. Severe infection rate reported in NTDT (non‐transfusion‐dependent thalassemia) was 5.2%, which is higher as compared to the present study. However, the rate of infection increased following splenectomy .…”
Section: Discussionsupporting
confidence: 73%
“…Overall rate of infections per year in the present study was 3.03 ± 0.45 per year per patient. Severe infection rate reported in NTDT (non‐transfusion‐dependent thalassemia) was 5.2%, which is higher as compared to the present study. However, the rate of infection increased following splenectomy .…”
Section: Discussionsupporting
confidence: 73%
“…There are many thalassemiarelated complications which are found to increase morbidity and mortality of the disease that includes heart failure [5][6][7], pulmonary hypertension [8][9][10][11], extramedullary hematopoiesis [12][13][14][15], osteoporosis [16,17], cholelithiasis, infections [18][19][20], thrombosis [21][22][23] and endocrinopathies [24,25]. Several studies in the past few years have shown the clinical risk factors for disease-related complications that include: advanced age, anemia, splenectomy, iron overload, severe thalassemia genotypes and iron chelation therapy [9,19,[26][27][28][29][30]. Some of these clinical risk factors had strong associations with the subgroup of thalassemia-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these clinical risk factors had strong associations with the subgroup of thalassemia-related complications. Iron overload is commonly found to be a significant risk factor for cardiac complications, infection and endocrine disorders [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical risk factors for bacterial infection in patients with thalassemia including splenectomy, iron overload, severe anemia, facial deformities, and gall-stones. Most of the studies on bacterial infections in patients with thalassemia have focused on those patients with thalassemia major [3]. Major causative organisms of bacterial infections in thalassaemic patients are Klebsiella spp , Yersinia enterocolitica, Escherichia coli, Pseudomonas aeruginosa, group B streptococci, Enterococcus spp.,Staphylococci Spp.…”
Section: Introductionmentioning
confidence: 99%